Balance Sheet Vulnerabilities of Mauritius During a Decade of Shocks - Imam, Patrick; Koehler, Rainer (Washington, D.C. : International Monetary Fund, 2010)
After reviewing the economic reform strategy of Mauritius for the past 10 years in the face of several external shocks, we apply a balance sheet analysis (BSA) focusing on currency, maturity, and intersectoral mismatches. In reviewing developments over this decade, we find that the currency and maturity mismatches have fallen across various sectors, and the intersectoral risks to each analyzed sector's balance sheet appear controllable. The government has implemented reforms in recent years that have contributed to general improvement in the balance sheet of the Mauritian economy and its subsectors. We conclude that from a BSA perspective, the macroeconomic vulnerabilities of Mauritius seem manageable, though vulnerabilities remain, and data gaps mean that more work will be needed to support these findings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet